2007
DOI: 10.1002/jemt.20492
|View full text |Cite
|
Sign up to set email alerts
|

Method of imaging low density lipoproteins by atomic force microscopy

Abstract: This short paper reports a simple method to image low density lipoproteins (LDL) using atomic force microscopy (AFM). This instrument allows imaging of biological samples in liquid and presents the advantage of needing no sample preparation such as staining or fixation that may affect their general structure. Dimensions (diameter and height) of individual LDL particles were successfully measured. AFM imaging revealed that LDL have a quasi-spherical structure on the x and y axis with an oblate spheroid structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
4
5
1
Order By: Relevance
“…Previous AFM studies have reported the sizes of the whole LDL fraction as 17 nm measured by Legleiter et al 16 and 23 AE 3 nm measured by Chouinard et al 19 The value reported by Legleiter et al 16 is within the range of our AFM measurements of LDL: 16.2 AE 1.4 nm for sd-LDL and 20.6 AE 1.9 nm for large LDL. On the other hand, Chouinard et al 19 just measured the scales of LDL particles without calculations in the topographical images, which would gives larger sizes of LDL particles than those by our analytical procedure.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Previous AFM studies have reported the sizes of the whole LDL fraction as 17 nm measured by Legleiter et al 16 and 23 AE 3 nm measured by Chouinard et al 19 The value reported by Legleiter et al 16 is within the range of our AFM measurements of LDL: 16.2 AE 1.4 nm for sd-LDL and 20.6 AE 1.9 nm for large LDL. On the other hand, Chouinard et al 19 just measured the scales of LDL particles without calculations in the topographical images, which would gives larger sizes of LDL particles than those by our analytical procedure.…”
supporting
confidence: 86%
“…On the other hand, Chouinard et al 19 just measured the scales of LDL particles without calculations in the topographical images, which would gives larger sizes of LDL particles than those by our analytical procedure. A previous study that used EM reported LDL particle sizes at 20-27 nm, 27 similar to those measured by EM in this study: 20.4 AE 1.4 nm for sd-LDL and 23.2 AE 1.4 nm for large LDL.…”
mentioning
confidence: 99%
“…Without the elimination process, the mean sizes were overestimated, which suggests that the larger size often estimated with DLS can be attributed to the existence of large particles such as aggregates. In the LDL particle cases, the mean sizes were 21.7 nm and 23.6 nm for sdLDL and lLDL, respectively, which agreed well with those reported in the literature [24,25]. These results suggest the effectiveness of the data processing technique proposed here.…”
Section: Elimination Of Large Scatterer Effectsupporting
confidence: 90%
“…the thickness of their LDL samples) was measured. In most previous AFM studies [5,[15][16][17], however, the average heights of individual LDL particles deposited on a substrate are generally less than 10 nm (e.g. 8.9 ± 1.9 nm at pH 7.4 in our current study).…”
Section: Effect Of Oxidation On the Stiffness Of Ldl Particlescontrasting
confidence: 58%